Managing the research university - Smith, Dean O., 1944- (New York ; Oxford : Oxford University Press, 2011)
This title provides a comprehensive background and discussion of the issues and challenges of managing a university's research enterprise. It provides a thorough background to research administration, covering all of the main issues confronting academic research administrators.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Universities and colleges -- United States -- Administration; Research institutes -- United States -- Administration